Anak Sebagai Pelaku Tindak Pidana Kesusilaan Dalam Prespektiff Kriminologi - Pieter, Salvadoris; Utami, Gusti Ayu (Bacarita Law Journal, 2024)
This research aims to determine and analyze the factors that cause moral crimes committed by children along with efforts to overcome them. This type of research is empirical legal research. The research results show that the most potential factors that can cause children to become perpetrators of crimes of decency or sexual violence are 1) family factors, 2) environmental factors, 3) educational factors, and 4) mass media factors. Efforts that can be made to overcome criminal acts of sexual violence committed by children are through early preventive efforts and repressive measures as a form of providing a deterrent effect to the child.